2015
DOI: 10.1007/s00401-015-1436-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals important role for TBK1 and OPTN mutations in frontotemporal lobar degeneration without motor neuron disease

Abstract: Frontotemporal lobar degeneration with TAR DNA binding protein 43 inclusions (FTLD-TDP) is the most common pathology associated with frontotemporal dementia (FTD). Repeat expansions in chromosome 9 open reading frame 72 (C9ORF72) and mutations in progranulin (GRN) are the major known genetic causes of FTLD-TDP; however, the genetic etiology in the majority of FTLD-TDP remains unexplained. In this study, we performed whole-genome sequencing in 104 pathologically confirmed FTLD-TDP patients from the Mayo Clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
253
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(264 citation statements)
references
References 63 publications
10
253
1
Order By: Relevance
“…Another study linked loss-of-function TBK1 mutations to both ALS and FTD (21). Finally, mutations in both TBK1 and OPTN are causal for both ALS and glaucoma (20,31). In this study, we observed that the ALS-associated mutants TBK1-E696K, OPTN-E478G, and OPTN-Q398X all interfere with efficient autophagic engulfment of damaged mitochondria.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Another study linked loss-of-function TBK1 mutations to both ALS and FTD (21). Finally, mutations in both TBK1 and OPTN are causal for both ALS and glaucoma (20,31). In this study, we observed that the ALS-associated mutants TBK1-E696K, OPTN-E478G, and OPTN-Q398X all interfere with efficient autophagic engulfment of damaged mitochondria.…”
Section: Discussionmentioning
confidence: 50%
“…Thus, the rate at which acutely damaged mitochondria are engulfed by autophagosomes may potently affect cellular homeostasis, with delays leading to toxic cellular insult. Consistent with this possibility, mutations in OPTN cause neurodegeneration, including both ALS and glaucoma, whereas TBK1 mutations also result in ALS and are implicated in frontotemporal dementia (FTD) (17)(18)(19)(20)(21)(22).…”
Section: Significancementioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, in a small cohort of patients with the rare combination of MS and ALS, approximately 80% carried a hexanucleotide repeat expansion in C9orf72 (128), suggesting these patients may have hyperactive immune responses to myelin antigens. Likewise, the recent identification of loss-of-function mutations in TBK1, a well-characterized regulator of innate immunity, as a cause of ALS/FTD (18,129,130) further reinforces the concept that immune dysregulation might be a characteristic feature of the disease. Despite the strong case for a connection between ALS/FTD and autoimmunity, there is also convincing evidence against the idea that ALS is itself a classical autoimmune condition, given that administration of immunosuppressive drugs including corticosteroids, azathioprine, and cyclophosphamide (alone or in combination), as well as plasmapheresis or intravenous Igs (IVIGs), has failed to alter the progression of the disease (131)(132)(133)(134)(135)(136)(137).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 76%
“…33 Another study suggested an additional more complex mode of inheritance for OPTN in neurodegenerative disease: a compound heterozygosity either within OPTN or together with the TBK1 gene. 34 We showed for the first time that OPTN 691_692insAG mutation is associated with AR ALS. In addition, the remarkable differences in frequencies of mutation carriage between MJ-ALS and MJ controls, and the replication of these results in AJ, with significantly increased risk for ALS in heterozygous carriers, strongly suggest that this mutation also has a dominant effect on ALS in the same populations.…”
mentioning
confidence: 80%